Suppressive effects of co-stimulatory molecule expressions on mouse splenocytes by anti-allergic agents in vitro - Jun-ichi Ito; Kazuhito Asano; Elzbieta Tryka; Ken-ichi Kanai; Sumiko Yamamoto; Tadashi Hisamitsu; Harumi Suzaki (Mediators of Inflammation)
The influence of anti-allergic drugs, epinastine hydrochloride (EP) and disodium cromoglycate (DSCG), on the co-stimulatory molecule expression was examined using in vitro cell culture technique. Spleen cells obtained from BALB/c mice 10 days after immunization with haemocyanin absorbed to aluminium hydroxide were cultured in the presence of 100.0 μg/ml haemocyanin and various concentrations of the agents. Low concentrations (< 1.5 2 10-4 M) of EP and DSCG did not influence spleen cell blastic activity induced by antigenic stimulation, whereas these agents caused significant inhibition of spleen cell activation when 2 × 10-4 M of the agents were added to cell cultures. EP and DSCG also did not affect blastic activity of sensitized splenic T cells by anti-CD3 monoclonal antibody stimulation even when these cells were cultured in the presence of 2 × 10-4 M of the agents. We next examined the influence of EP and DSCG on the expression of co-stimulatory molecules on spleen cells in response to antigenic stimulation. Sensitized spleen cells were cultured in the presence of 2 × 10-4 M of the agents and the expression of molecules were examined by flow cytometer 24 h later. EP and DSCG suppressed the expression of costimulatory molecules, CD40 and CD80, but not CD86, on splenic B cells which were enhanced by antigenic stimulation in vitro.